Damage-tolerant mechanical metamaterials designed by fail-safe topology optimization - Yukun Zheng; Wenke Qiu; Xuxi Liu; Zhou Huang; Liang Xia (Materials & Design)
Mechanical metamaterials are celebrated for their remarkable properties and advances in additive manufacturing, yet their damage tolerance in aerospace and other demanding environments remains underexplored despite their lightweight and high-strength design. This work proposes a novel approach to design damage-tolerant metamaterials using fail-safe topology optimization to ensure their mechanical performance remains resilient to local damages. The design strategy focuses on minimizing metamaterial’s weight while preserving its load-bearing capacity post-damage, with the effective bulk modulus used as a measure. To enhance performance under varying, complex, or uncertain loads, an isotropy constraint is incorporated into the design. The proposed method involves a trade-off where the metamaterial’s enhanced damage tolerance is achieved by slightly reducing the load-bearing capacity of the intact structure. By tuning structural redundancy, the method facilitates the development of lightweight, mechanically robust structures. Numerical simulations and experimental tests on three-point bending beam structures made from periodically ordered damage-tolerant metamaterials show that the proposed design maintains load-bearing capacity after damage while enhancing safety and reliability by preserving structural integrity and load transfer paths.